Addition of Some Primary and Secondary Amines to Graphene Oxide, and Studying Their Effect on Increasing its Electrical Properties (Baghdad Science Journal, 2016)
Previously many properties of graphene oxide in the field of medicine, biological environment and in the field of energy have been studied. This diversity in properties is due to the possibility of modification on the composition of this Nano compound, where the Graphene oxide is capable of more modification via addition other functional groups on its surface or at the edges of the sheet. The reason for this modification possibility is that the Sp3 hybridization (tetrahedral structure) of the carbon atoms in graphene oxide, and it contains many oxygenic functional groups that are able to reac with other groups. In this research the effect of addition of some amine compounds on electrical properties of graphene oxide has been studied by the preparation of graphene oxide - amino containing compound, which could be classified under Nano carbon compounds containing nitrogen (N-doped carbon nanomaterials). These amines are used as expanders for the distance between the layers of graphene oxide (spacers), and thus prevent agglomeration of graphene oxide layers in addition to enhanced electric properties of graphene oxide. The following amines (thiocarbohydrazide(TCH),o-phenylenediamine(oPD) and poly aniline(PAni)) were used for the preparation of the corresponding amino graphene oxide (GO-TCH, GO-containing Benzoimidazol & benzoxazole, and GO-PAni), and characterized by X-RAY diffraction (XRD) ,infra red spectrum (FTIR) and atomic force microscope (AFM) , also the electrical properties of these materials were studied using inductance, capacitance, and resistance ( LCR) measurements.